KEARIFAN LINGKUNGAN: TRADISI MASYARAKAT JAWA DALAM UPAYA MENGHORMATI ENTITAS ALAM - Ahmad Miftahudin Thohari (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The environment or nature has an important position for human life. Without nature, man can be said to be impossible to live. Nature is a place where humans live, so maintaining, caring for, and beautifying the existence of nature into something that must be done by humans. Man is an integral part of nature itself. So that humans have a responsibility to maintain and preserve it. However, when technological sophistication and the advancement of civilization reached the heart of human consciousness in the modern era, it became the cause of environmental damage (environmental crisis). And, today the environmental crisis has become a vital problem for human life. It then demands the return of human awareness of the fate of nature or the environment in various ways. Through the library research method in this article intends to provide a description of how the concept of environmental wisdom (ecosophy) java man positions nature in his life consciousness, following also presented some Javanese traditions related to respect and preservation of nature as an entity that has given it life.